(3TQM GdbUjOI GdehSheI HCe GdbQi aj eOM NjQ GdhQis - (3eMeO Hf YHO GdefYe Hf eMeO GdLhLQj,J (B889 (3g` s ((3CMeO Hf eMeO GdSNGhi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NU fHjfG eMeO Udi Gddg Ydjg hSde HYehe GdEQSGd hcGf ef GMSf eG eOM Hg ef GdefXhe eG fXeg GdTjN GHf gdGd GdUfgGLi fGXe GdHQO I GTJgQ HGdHhUjQi aGSJNQJ Gddg JYGdi hhVYJ YdjgG TQMG s
(3BNQgG (B:s
(3Je hcedq s
(3HgG fXGe GdJYbjHIs
(3TQM dbUjOI GdHQOI ddHhUjQis
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B130s
Keywords: (3GdCOHs